Hubungan Pola Pengasuhan Dan Sikap Orangtua Dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita: Relationship of Parenting Pattern and Parental Attitude with Acute Respiratory Infections in Children Under 5 Years - Oky Rahma Prihandani; Jihan Fatmawati; Kanti Ratnaningrum (Universitas Ahmad Dahlan, 2023)
Acute respiratory infections (ARIs) is the leading cause of death in children under 5 years oldThe objective of this study was to determine the relationship between parenting pattern and parental attitude with the incidence of ARIs in children under 5 years old at Karangkemiri Village, Banyumas. This was a cross sectional study with the subjects of 46 mothers. Data was analyzed using Fisher’s Exact Test and Logistic regression. The results showed that the incidence of ARIs in children under 5 years was 32.6%. Bivariate analysis showed significant differences in feeding habit, parenting habit, and parental attitude on the incidence of ARIs with a value of 0.023, 0.003, and 0.023 respectively. Meanwhile, there is no relationship between the habit of providing health services on the incidence of ARIs with a value of 0.244. The most important factor in this study was parenting habit